Legalizing illegalities? Land titling and land tenure security in informal settlements - Bwalya Umar, Bridget; Kapembwa, Julius; Kaluma, Ketiwe; Siloka, Lawrence; Mukwena, Dipuo (Frontiers in Sustainable Cities, 2023)
This study investigated how land rights formalization had affected land tenure security among landowners in two informal settlements of Lusaka and Chongwe districts, Zambia. It explored how social norms on land inheritance, decision making over land, marital trust and land related conflicts had been affected by the changed nature of land rights. Data was collected through a questionnaire survey of all the 302 households that had obtained title deeds at the time of the survey, two 3-in-1 focus group discussions and four key informant interviews. Results suggest that land tenure security is now a reality for residents that hitherto lived under constant threat of eviction. Landowners have benefitted from the formalization initiative through land laws and local norms that allow equitable access to land. Land rights formalization has curtailed land rights for secondary claimants such as extended family members, in preference for man, spouse and biological children. A sense of ownership undisputedly increased for men and women in the two study sites. About 50% of the respondents in both study sites indicated that formalization of land rights had not resulted in family conflicts. At least one-third from both sites reported an increase in love and trust between spouses after land rights formalization. About half of the respondents reported that no change in decision-making authority had occurred for men while 42% reported an increase. Formalizing land rights in informal settlements has entailed legalizing illegalities as regulations on plot boundaries are set aside by the state to achieve its aspirations of providing land tenure security to poor urbanites who would not otherwise have recourse to legal or regularized land. We recommend that caution be taken in promoting what is unarguably a pro-poor initiative to ensure that such initiatives should not incentivize future land encroachments.